A Study of Prevalence of Hypertension and Pre-Hypertension and Its Associated Risk Factors in Rural Area Of Madhya Pradesh - Anshuman Sharma; Sanjay Kumar Gupta; Sanjay S Agarwal; Manmohan Gupta; Shweta Shrivastava (Medsci Publications, 2015)
Introduction: As it is hidden beneath an outwardly asymptomatic appearance, the disease does immense harm to the body in the form of 'Target Organ' damage; hence the WHO has named it the 'Silent Killer'. A majority of the rural population in India have inadequate access to healthcare. Clinic-based (Opportunistic) screening of hypertension will not screen and detect a large pro- portion of adult hypertensives. Objective of the study was to find out the prevalence of hypertension and various risk factors asso- ciated with hypertension in the rural area. Methodology: It was a community based cross sectional study in rural area. Observation: Majority of (44.4%) individuals belongs to 30-40 years of age in the study group, most of participants in the study were illiterate 56.6 %, majority of respondents belong to middle socio-economic class 32.6% .Prevalence of pre-hypertension and hypertension among studied population were 40.8% &14.2% re- spectively, hypertensive's & pre-hypertensive's shows no signifi- cant relationship between smoking but significant relationship found between the amounts of alcohol consumption with hyper- tension. The significant relationship was observed between their socio economic status with hypertensive and pre hypertensive. Conclusions: There is a high prevalence of pre- hypertension in rural area of Bhopal, this group required more attention to pre- vent further development of disease and its complication.